Co-authorship networks: Collaborative research structures at the journal level - José António C. Santos; Margarida Custódio Santos (Tourism & Management Studies)
Present-day research is, in most cases, the outcome of collaborative research, as evidenced by the fact that most papers are authored by two or more researchers. This study’s general goal was to examine the evolution and structure of scientific collaborative networks revealed by papers published in the Tourism & Management Studies journal over a five-year period, from 2011 to 2015, as well as to represent these networks graphically. In this paper, we seek to offer a clear assessment of intra-institutional, inter-institutional and international collaborations and to identify primary author networks and the role of gender in their composition. To reach these goals, we used a combination of bibliometric analysis with social network analysis. The results demonstrate that geographic proximity and linguistic affinity play a substantial role in scientific collaboration between institutions. In fact, most papers result from collaborative research involving two or more authors from the same institution. A gender analysis of the universe of authors and co-authors and of the role of women in the composition of co-authorship networks demonstrated that most networks include women and that, in most networks, women have a leading position, which is consistent with their weight (51.3%) in the universe of authors. This is one of the first studies to demonstrate that women are taking the lead in tourism and management research.